Regenerative medicine for peripheral artery disease - Mohler, Emile R., III; Annex, Brian H. (Academic Press is an imprint of Elsevier, 2016)
Regenerative Medicine for Peripheral Artery Disease is a comprehensive and up-to-date resource on the use of regenerative medicine for the treatment of peripheral arterial disease. This reference includes a general overview of regenerative medicine and covers important vascular topics, including intermittent claudication and critical limb ischemia, with important mechanisms clearly presented in full color images throughout the book. This important reference includes clear and concise information on both human clinical trials, as well as important and pertinent animal studies, and is a must-have reference for researchers and practitioners of peripheral artery disease.